Biomarker Research - Hsueh, Chung-Tsen; Wang, Hong; Liu, Delong
Biomarker Research is an open access, peer-reviewed journal that encompasses all aspects of biomarker investigation. Biomarker Research aims to publish original discoveries, novel concepts, commentaries and reviews related to biomarker investigation from all biomedical disciplines. The study of biomarkers has evolved rapidly in the advance of personalized medicine and individual health. The identification and validation of biomarkers in drug discovery/development and in disease diagnosis, treatment, prognosis, and prevention play an essential role in the genome era. With a quick turnaround time from submission to publication and online feedback from readers, Biomarker Research strives to provide fast dissemination of novel findings and new knowledge.